Numerous Sublinear Sets of Holes in Sediment on the Northern Mid-Atlantic Ridge Point to Knowledge Gaps in Understanding Mid-Ocean Ridge Ecosystems - Vecchione, Michael; Bergstad, Odd Aksel (Frontiers in Marine Science, 2022)
On 13 July 2004, during an expedition exploring biodiversity along the northern Mid-Atlantic Ridge, an ROV dive recorded videos of numerous sublinear sets of holes in sediment at ca. 2,082 m depth. The location was north of the Azores. Each set appeared track-like. Lengths of individual series ranged from < 1 m to many meters. Each was straight or gently curved. Some series intersected or crossed. Close examination of the holes showed them to be elongate, with the long axis parallel to the axis of the series. The holes were ca. 6 × 1.5 cm, with distance between holes similar to hole length. The holes that appeared to be most recently formed were each surrounded by raised sediment. Holes that appeared older were partly filled with sediment and the raised surrounding sediment was less obvious. Overall, these lebensspuren created small-scale heterogeneity in the local soft-bottom benthic ecosystem. The source of the holes or how they were constructed is unknown, but the raised sediment may indicate excavation by an infaunal organism or digging and removal by e.g., a feeding appendage of a large epifaunal animal. None of our closeups showed any sign of living organisms inhabiting the holes. Whether the holes were connected beneath the sediment surface was not visible. The traces observed are reminiscent of ichnofossils reported from deep marine facies. We hope that future studies of the lebensspuren we report here will resolve the mystery of what created them.